The Biological Activity of Kumchura Rhizome to Melon Fly: I. Crude Kumchura Bioactivity - Edhi Martono (Jurnal Perlindungan Tanaman Indonesia, 1996)
Kumchura (Kaempferia galanga, L.) rhizome, a herbal medicine and condiment used in many Asian countries, was known to possess licicidal quality. To ensure whether this quality extend to other insects, kumchura rhizome preparation was applied to eggs, larvae and adults of the melon fly, Bactrocera cucurbitae, Coquillet. Crude preparation of the rhizome was mixed with larval diet which was also served as a common artificial egg-hatching medium. The preparation proved to be ovicidal at minimum concentration ratio of 1 :4, kumchura:larval diet. No such larvicidal effects were seen at the same ratio, the effects observed were larval development inhibition and delay. In the repellency tests, proportionally less melon flies were found on diet containing kumchura, but no effect on oviposition was observed.